The witch collector ebook - Weaks, Charissa (Witch Walker, 2021)
Every harvest moon, the Witch Collector rides into our valley and leads one of us to the home of the immortal Frost King, to remain forever. Today is that day—Collecting Day. But he will not come for me. I, Raina Bloodgood, have lived in this village for twenty-four years, and for all that time he has passed me by. His mistake. Raina Bloodgood has one desire: kill the Frost King and the Witch Collector who stole her sister. On Collecting Day, she means to exact murderous revenge, but a more sinister threat sets fire to her world. Rising from the ashes is the Collector, Alexus Thibault, the man she vowed to slay and the only person who can help save her sister. Thrust into an age-old story of ice, fire, and ancient gods, Raina must abandon vengeance and aid the Witch Collector or let their empire—and her sister—fall into enemy hands. But the lines between good and evil blur, and Raina has more to lose than she imagined. What is she to do when the Witch Collector is no longer the villain who stole her sister, but the hero who's stealing her heart? The Witch Collector is book one in a thrilling romantic fantasy series, perfect for fans of Naomi Novik, Sarah J. Maas, and Jennifer L. Armentrout.